Дослідження динамічних характеристик верстата з механізмом паралельної структури - Осадчий, C. І.; Зозуля, В.А. (Видавництво Львівської політехніки, 2011)
This article explores the dynamics of the mechanism with parallel kinematics with help of the definition of mathematical models describing the relationship between changes in control signals, disturbances and coordinate platform center of mass.
Keywords: механізм з паралельною кінематикою; структурна ідентіфікація; система керування